Tecnologia exponencial e os novos desafios da sociedade contemporânea - Borges Corrêa, Sílvia; Jacubowski Correia Dubeux, Veranise; Terra, Simone; Jacques, Daniela (Boletim Técnico do Senac, 2017)
Veranise Jacubowski Correia Dubeux, Sílvia Borges Corrêa, Daniela Jacques e Simone Terra entrevistam Marcos Cavalcanti